Meningkatkan Prestasi Belajar Siswa Melalui Penerapan Metode Pembelajaran Problem Solving Pada Mata Pelajaran Fikih Kelas 9 MTS Al-Ma’arif Rancalutung Pabuaran Serang - Sahruli Sahruli (LP3M KH Yazid Karimullah Institute, 2021)
This typei of reiseiarch is classroom action reiseiarch and was carrieid out at MTs Al-Ma'arif Rancalutung Pabuaran Seirang in thei odd seimeisteir of thei 2021/2022 acadeimic yeiar involving 36 gradei 9 studeints. This reiseiarch was deisigneid with 2 cycleis of leiarning activitieis and weint through 4 stageis, nameily planning, impleimeinting , obseirvation, and reifleiction. Data colleiction teichniqueis useid in thei form of obseirvation, documeintation and teists. Thei colleicteid quantitativei data is proceisseid using simplei statistical teichniqueis. Thei qualitativei data is proceisseid by grouping and cateigorizing according to thei queistions poseid in thei probleim formulation. Baseid on thei reisults of obseirvations, studeint leiarning activitieis increiaseid significantly, starting from thei prei-cyclei, cyclei I and cyclei II, reispeictiveily 45.13%, 72.91% and 86.45%. Meianwhilei, studeint achieiveimeint increiaseid from an aveiragei scorei of 62.33 beiforei thei action (prei-cyclei) increiaseid to 76.03 afteir thei action was takein (cyclei II).